Lipoprotein Glomerulopathy-Like Lesions in Atherosclerotic Mice Defected With HDL Receptor SR-B1 - Liao, Jiawei; Bai, Jie; An, Xiangbo; Liu, Yang; Wang, Yuhui; Liu, George; Huang, Wei; Xia, Yunlong (Frontiers in Cardiovascular Medicine, 2021)
High-density lipoprotein (HDL) homeostasis is important in maintaining both cardiovascular and renal health. Scavenger receptor class B type 1 (SR-B1), the major HDL receptor in mammals, plays a crucial role in reverse cholesterol transport and HDL metabolism. Evidence from mouse study has well demonstrated that HDL disorders caused by Srb1 inactivation accelerate atherosclerosis and even induce lethal cardiovascular diseases. However, the renal consequences of Srb1 dysfunction are still unknown. Here we explored this issue in both Srb1 knockout (Srb1-/-) mice and atherosclerotic low-density lipoprotein receptor knockout (Ldlr-/-) mice with Srb1 deletion. Our data showed that no apparent renal damage was observed in 5-month-old Srb1-/- mice fed on standard rodent chow diet as well as Srb1-/- mice fed on a high-fat diet (HFD) for 12 weeks. However, 5-month-old Srb1/Ldlr-/- mice fed on rodent chow had increased urinary albumin excretion and developed spontaneous intraglomerular Oil-red O (ORO)-positive lipoprotein deposition that is similar to lesions observed in human lipoprotein glomerulopathy (LPG). HFD feeding accelerated LPG-like lesions in Srb1/Ldlr-/- mice, inducing severe proteinuria and significantly promoting intraglomerular ORO-positive lipoprotein deposition. Interestingly, probucol reversed HFD-induced HDL disorders and almost fully abrogated LPG-like lesions in Srb1/Ldlr-/- mice. In conclusion, the present study demonstrates that SR-B1 dysfunction leads to LPG-like lesions in atherosclerotic mice, which could be rescued by probucol. SR-B1 loss-of-function mutant carriers therefore might be susceptible to developing metabolic nephropathy in addition to cardiovascular diseases, and probucol might be a potential therapeutics.